2017
DOI: 10.1021/jacs.7b02428
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Transfer Dissociation Reveals Surprising Favorability of Zwitterionic States in Large Gaseous Peptides and Proteins

Abstract: Structural characterization of proteins in the gas phase is becoming increasingly popular, highlighting the need for a greater understanding of how proteins behave in the absence of solvent. It is clear that charged residues exert significant influence over structures in the gas phase due to strong Coulombic and hydrogen-bonding interactions. The net charge for a gaseous ion is easily identified by mass spectrometry, but the presence of zwitterionic pairs or salt bridges has previously been more difficult to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
81
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 47 publications
8
81
1
2
Order By: Relevance
“…[1] However, there is growing experimental evidence that indicates that such charge separation is possible in the gas phase for systems as small as two amino acids. [2,3,4] Techniques used to elucidate the location and arrangement of salt bridges in the gas phase include computational studies [5], ion mobility [6], ion spectroscopy [2], and interpretation of fragmentation via mass spectrometry [4,7,8]. Many of the experimental techniques rely upon some form of calculation to provide a precise prediction of zwitterionic structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] However, there is growing experimental evidence that indicates that such charge separation is possible in the gas phase for systems as small as two amino acids. [2,3,4] Techniques used to elucidate the location and arrangement of salt bridges in the gas phase include computational studies [5], ion mobility [6], ion spectroscopy [2], and interpretation of fragmentation via mass spectrometry [4,7,8]. Many of the experimental techniques rely upon some form of calculation to provide a precise prediction of zwitterionic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bonner et al have shown that photoexcitation of net positively-charged ions that can contain anionic sites, specifically carboxylates, lead to fragmentation analogous to that observed with electron-based dissociation techniques. [7] This technique directly probes for the presence of zwitterionic sites, by photoactivation of the ion. Other light-based activation techniques such as infrared multiple photodissociation spectroscopy also show the ability to directly identify the presence of zwitterionic interactions by revealing unique vibrational signatures of the carboxylate functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the large importance of studying the main mechanisms of structural changes in amino acid molecules under the action of low-energy electrons, the body of relevant data is quite scarce [3]. One of the most reliable methods for studying the structure of matter and the physical processes occurring in it is the mass spectrometry, because it allows obtaining useful information about the fragmentation of original molecules in the gas phase [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на безоговорочную значимость изучения основных механизмов структурных изменений в молекулах аминокислот под действием низкоэнергетических электронов, данных такого рода довольно мало. Одним из важных методов исследования структуры вещества и физических процессов, происходящих в нем, является масс- спектрометрический, который позволяет методом электронного удара получать всестороннюю информацию о фрагментации исходных молекул в газовой фазе [4]. Целью настоящей работы является исследование процесса ионизации глутаминовой кислоты и глутамина в газовой фазе масс-спектрометрическим методом при различных температурах испарения исходного вещества, а также измерение энергетических зависимостей образования положительных ионов материнской моле-…”
unclassified
“…(12) Естественно, что более полный анализ процессов (1)−(12) можно провести с привлечением теоретических расчетов энергий связи. В случае процессов фотоионизации это сделано в [4].…”
unclassified